2018
DOI: 10.1002/lary.27117
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant provider awareness of vaccination guidelines

Abstract: NA. Laryngoscope, 128:2145-2152, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although the pneumococcal vaccination recommendations have been in effect for many years now, it is concerning how drastically variable the rates are from full compliance. 10 One explanation could be secondary to a lack of provider awareness. In 2018, the results of a survey of 256 providers revealed that knowledge of vaccination guidelines in patients undergoing cochlear implantation was high; however, understanding of age group-specific immunizations and recording of vaccinations into a database were both reported as low.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the pneumococcal vaccination recommendations have been in effect for many years now, it is concerning how drastically variable the rates are from full compliance. 10 One explanation could be secondary to a lack of provider awareness. In 2018, the results of a survey of 256 providers revealed that knowledge of vaccination guidelines in patients undergoing cochlear implantation was high; however, understanding of age group-specific immunizations and recording of vaccinations into a database were both reported as low.…”
Section: Discussionmentioning
confidence: 99%
“…This notion of perceived mixed efficacy is considered to be a limiting factor in some providers prioritizing immunization. 10 To date, there are no human studies correlating pneumococcal vaccination and meningitis within the cochlear implant population cohort. 16 This will require an extended data collection period, given the already low incidence of meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations